Executive Committee Minutes 2017-11-02 - Academic Senate:::::::::
Agenda Approved. Minutes of 10/5 and 10/19 approved. Chair Report. Dual Language Historical Research Certificate approved for Senate consent calendar. President Report. Provost Report. CFA Report. Vice Chair Report. Vice President of Administration and Finance Report. Preliminary Discussion of Faculty Retreat and Topics. Discussion about inviting the Mayors of Rohnert Park and Cotati to the Senate. EPC Report. Senate agenda approved. Associated Student Report.